2006
DOI: 10.1523/jneurosci.2755-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of the Developing Rat Brain Reveals That the Most Dramatic Regional Differentiation in Gene Expression Occurs Postpartum

Abstract: Neural development involves the expression of ensembles of regulatory genes that control the coordinate and region-specific expression of a host of other genes, resulting in the unique structure, connectivity, and function of each brain region. Although the role of some specific genes in neural development has been studied in detail, we have no global view of the orchestration of spatial and temporal aspects of gene expression across multiple regions of the developing brain. To this end, we used transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 44 publications
6
106
0
Order By: Relevance
“…These factors, combined with a compensatory increase in cerebral blood flow and enhanced glucose extraction from the blood, may provide neuroprotection to the developing brain during hypoglycemia [21,37]. Differences in the developmental stage of the cells, the number and function of neurotransmitter receptors, molecular and biochemical pathways of energy metabolism, susceptibility to respiratory depression and glucose reperfusion injury may also be responsible for the age-related vulnerability during hypoglycemia [7,20,30,32]. Similar, age-related resistance of the early postnatal brain has been demonstrated in other models of perinatal injuries, such as hypoxia-ischemia [11,36].…”
Section: Discussionmentioning
confidence: 99%
“…These factors, combined with a compensatory increase in cerebral blood flow and enhanced glucose extraction from the blood, may provide neuroprotection to the developing brain during hypoglycemia [21,37]. Differences in the developmental stage of the cells, the number and function of neurotransmitter receptors, molecular and biochemical pathways of energy metabolism, susceptibility to respiratory depression and glucose reperfusion injury may also be responsible for the age-related vulnerability during hypoglycemia [7,20,30,32]. Similar, age-related resistance of the early postnatal brain has been demonstrated in other models of perinatal injuries, such as hypoxia-ischemia [11,36].…”
Section: Discussionmentioning
confidence: 99%
“…During this period, regions such as the hippocampus, the visual and auditory cortices, and the striatum undergo rapid development characterized by the morphogenesis and synaptogenesis that make them functional [54,83]. For any given region, early malnutrition have a greater effect on cell proliferation, thereby affecting cell number [81,91].…”
Section: Nutrition and Mental System Developmentmentioning
confidence: 99%
“…Neuroanatomical studies using Golgi staining techniques showed that malnutrition caused a significant disruption in pyramidal cells of the cerebral cortex, a reduction in the density of cortical dendritic spines, and a decrease in both the width of cortical cells and the complexity of the dendritic branching of the cortex [44]. For any given region, early malnutrition reduced the speed of cell proliferation and the total cell number in rat [81].…”
Section: Nutrition and Mental System Developmentmentioning
confidence: 99%
“…Thus, extrapolation from mouse to man may not be possible on specific days of pregnancy, but can be construed from prenatal and postnatal peaks of neurogenesis, gliogenesis and neuron/glia differentiation and migration (Susser et al 1999). The choice of postnatal days 35 and 56 in our studies are based on a large group of supportive literature (Avishai-Eliner et al 2002;Boksa et al 2003;Kaufmann, 2000;Morgane et al 2002;Romijn et al 1991;Spear, 2000;Susser et al 1999) denoting E0-E10 in rodents as equal to first trimester in humans, E11-E19 as equal to 2 nd trimester, P0-P7 as equal to third trimester (Morgane et al 2002;Stead et al 2006), P35 as equal to adolescence (Spear, 2000) and P56 as equal to early adulthood (Spear, 2000).…”
Section: Animals and Infectionmentioning
confidence: 99%